Bovine fetal testicular development in the Nellore breed - De Souza, Juliana Stephany [UNESP]; Miguel, Maria Carolina Villani [UNESP]; Maioli, Marcos Antônio [UNESP]; Neto, Arthur Nelson Trali [UNESP]; Arana, David Giraldo [UNESP]; Laurini, Alexandre Rossi [UNESP]; Nogueira, Guilherme De Paula [UNESP] (Universidade Estadual de Londrina, 2017)
The study of gonadal development improves the understanding of factors that can influence the reproductive development process. This study aims to characterize bovine fetal testicular development and the testosterone level in the Nellore breed. For the study, 162 bovine fetuses aged between 3 and 8 months were collected from Nellore cows at a local abattoir. The fetal age was estimated by DP=8.4+0.087L+5.46√L, where DP is the estimated pregnancy day and L represents fetal length. The fetal gonadal weight (g), width (cm), and thickness (cm) were measured. Thereafter, the gonads were submitted to classic histology processes in 3-μm-thick slices cut at 210 μm intervals. The Sertoli cells, Leydig cells, and germ cells were counted. Blood samples were collected from umbilical cords for testosterone levels. The data were analyzed using the Spearman correlation test followed by Principal Component Analysis and one-way ANOVA to compare the averages between months. The testicular weight and volume were found to have a positive correlation with the numbers of Sertoli cells (r = 0.84; p < 0.0001 and r = 0.92; p < 0.0001, respectively), Leydig cells (r = 0.80; p < 0.0001 and r = 0.90; p < 0.0001, respectively), and germ cells (r = 0.84; p < 0.0001 and r = 0.93; p < 0.0001, respectively) and to be negatively correlated with testosterone plasmatic concentration (r = -0.31; p = 0.0001 and r = -0.22; p = 0.006, respectively) during pregnancy. After the fifth month, the numbers of Sertoli cells, Leydig cells and germ cells differed (p < 0.0001) from the following gestational months. The highest testosterone concentration (p = 0.007) was observed in the fifth month of gestation and was followed by a concentration decrease in the seventh and eighth months. The increase in cell quantity was responsible for the increase in testicular weight and volume during fetal development. On the other hand, the testosterone concentration followed the increase in testicular weight and volume until the 7th month of gestation and regressed during the 8th and 9th months, in addition to the increase in cell number.
Keywords: Germ cells; Pregnancy; Sertoli cells; Testicle interstitial cells; Testosterone concentration